Identification of Critical Land based on Land Damage Standard Criteria in Manten Sub Watershed, Malang City - Anisah Aprilia Garciah; Maroeto Maroeto; Purnomo Edi Sasongko (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Land is an important part of the watershed because it is where the hydrological process occurs. There are several problems that can lead to land damage, especially in the downstream area of the watershed, precisely in the Manten Sub-watershed because it has the potential to become critical land. Therefore, this research was conducted with the aim to overcome the existing problems, it is necessary to identify the standard of land degradation in the Manten Sub-Watershed area in accordance with PP No. 150 of 2002. Manten sub-watershed covers 4 sub-districts namely Wajak, Poncokusumo, Tajinan, and Bululawang. Land use in Manten sub-watershed is divided into 3, namely rice fields, kailyards and fields. Based on the results of the analysis of all land use in Manten Sub Watershed, all parameters that have been observed do not exceed the critical threshold criteria except for the redox parameter has a very low value of <200mV. However, this condition can still be improved with proper management such as improving soil aeration using the addition of organic materials so as to increase oxygen levels in the soil and increase redox values.